Chromosome size matters: genome evolution in the cyperid clade. (7th November 2022) - Elliott, Tammy L; Zedek, František; Barrett, Russell L; Bruhl, Jeremy J; Escudero, Marcial; Hroudová, Zdenka; Joly, Simon; Larridon, Isabel; Luceño, Modesto; Márquez-Corro, José Ignacio; Martín-Bravo, Santiago; Muasya, A Muthama; et al.
Abstract: Background and Aims: While variation in genome size and chromosome numbers and their consequences are often investigated in plants, the biological relevance of variation in chromosome size remains poorly known. Here, we examine genome and mean chromosome size in the cyperid clade (families Cyperaceae, Juncaceae and Thurniaceae), which is the largest vascular plant lineage with predominantly holocentric chromosomes. Methods: We measured genome size in 436 species of cyperids using flow cytometry, and augment these data with previously published datasets. We then separately compared genome and mean chromosome sizes (2C/2 n ) amongst the major lineages of cyperids and analysed how these two genomic traits are associated with various environmental factors using phylogenetically informed methods. Key Results: We show that cyperids have the smallest mean chromosome sizes recorded in seed plants, with a large divergence between the smallest and largest values. We found that cyperid species with smaller chromosomes have larger geographical distributions and that there is a strong inverse association between mean chromosome size and number across this lineage. Conclusions: The distinct patterns in genome size and mean chromosome size across the cyperids might be explained by holokinetic drive. The numerous small chromosomes might function to increase genetic diversity in this lineage where crossovers are limited during meiosis.